ARTIFICIAL INTELLIGENCE IN MEDICINE: NEW OPPORTUNITIES IN DIAGNOSIS AND TREATMENT - Qahramonov Davron Dilshod o‘g‘li (World Scientific Research Journal, 2025)
The development of artificial intelligence (AI) technologies in modern medicine is creating new opportunities in diagnostic and treatment processes. AI algorithms are playing an important role in early disease detection, clinical decision support, and the development of individualized treatment plans. This article analyzes the importance of artificial intelligence in medicine, its main applications in diagnosis and treatment, as well as existing challenges and future prospects